Influence of casual distributions on resonant properties of ensembles of nonlinear oscillators - Buts, V.A. (Вопросы атомной науки и техники, 2009)
It is shown, that properties of ensembles of nonlinear oscillators each of which makes chaotic movement, can essentially differ from properties separate oscillators. In particular, is shown, that dynamics of average values of ensembles can essentially depend on the statistical characteristics of separate oscillators.